Old age from a critical perspective: in search of a theory - Bernardini, Maria Giulia (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2025)
The essay employs the conceptual framework of critical legal theories to highlight several key issues related to the equal legal recognition of older individuals and their rights (e.g., vulnerability, institutionalization, and ageism as a specific form of oppression), arguing for the necessity of developing a genuine critical theory of law concerning old age.